GAMBARAN PENERAPAN KOMUNIKASI TERAPEUTIK PERAWAT PADA PASIEN DI RUANG PERAWATAN INTENSIVE CARE UNIT (ICU) RUMAH SAKIT UMUM DAERAH TOBELO - Blandina, Olivia Asih; Karu, Feki (Jurnal Online Keperawatan Indonesia, 2024)
The background of this research is that therapeutic communication has four stages, namely pre-interaction, orientation, and work and termination stages. This study aims to determine the description of the application of therapeutic communication by nurses to patients in the Intensive Care Unit (ICU). This study uses a qualitative method. The results of research R1, R2, R3, and R4 state that nurses can understand actions towards patients, regardless of the patient's status or background. The orientation stage is the stage that begins with a meeting with the patient. R1 introducing himself by establishing an initial rapport with the patient is an important first step in establishing a therapeutic relationship. This research focuses on four main aspects, namely communication about care, the goals and functions of each treatment, motivation and psychological environment, communication with total care and partial care patients, and communication with total care patients. The research concludes that communication with total care patients was more effective than with partial care patients because patients more easily received clear and detailed responses from health workers. This research also emphasizes the importance of transparency and concern for patients, as well as the importance of communication with partial care patients.